The Dutch Republic and the Spanish Slave Trade, 1580-1690 - Antunes, Cátia; Negrón, Ramona (TSEG - The Low Countries Journal of Social and Economic History, 2022)
This article investigates the reason why groups of merchants operating from the Dutch Republic, particularly from Amsterdam, decided to take part in the exploitation of the Spanish Empire, through a very particular type of activity, that of the slave trade. We argue that Amsterdam-based merchants were heavily engaged, through various organizational forms, in supplying Spanish American markets with enslaved Africans. This participation was rewarded with a path for access to Spanish American silver, at the time the essential exchange mechanism for entry and expansion in the Mediterranean and Asian trades.